(untitled) (JOURNAL OF ADVANCES IN MATHEMATICS, 2014)
The concept of Semi-Bc-continuous functions in topological spaces is introduced and studied. Some of their characteristic properties are considered. Also we investigate the relationships between these classes of functions and other classes of functions.